A Virtual Physics-based Approach to Multiple Odor Sources Localization - Xiaoping Ma; Yuli Zhang; Yanzi Miao (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
The detection of an odor source location has been enhanced by using multiple plume-tracing mobile robots. So far, many researchers focus on locating a single source in varied environments. The present study is concerned with the problem of multiple chemical sources localization using multi-robot system. In this study, multiple groups of robots were used and coordinated by a multi-robot cooperation strategy with virtual physics force, which includes structure formation force, goal force, repulsion force and rotary force. In order to test the effectiveness of the proposed strategy, plume model with two sources was constructed by computation fluid dynamics simulations. Simulation experiment discussed the influence of the varied frequencies of wind direction/ speed and methane release with different initial positions of multiple groups to the search performance. Simulation comparison experiments using three kinds of plume tracing algorithms: chemotaxis, anemotaxis and fluxotaxis were carried out respectively and the comparative result about three plume tracing algorithms was illustrated.